Between Assimilation and Discrimination. Immigrants' Religiosity in Europe - Francesco Molteni (Culture e Studi del Sociale)
Given the sharp increase in migration flows, the issue of immigrants’ religious assimilation and its impact on integration and discrimination has become a hot topic. This article refers to the debate between assimilation and reaction theories in order to shed light on the effects of both the destination context and the passage of time on immigrants’ religiosity. Using the nine waves of European Social Survey data, I show that non-Muslim migrants display tendencies towards assimilation, with second generations being more similar to the native population than to the first generations in terms of levels of religiosity. Conversely, Muslim migrants are seen to resist more to assimilation pressures, thus reinforcing a reading based more on ethnic reactions. In addition to this, the data clearly show that there is a specific sector of the migrant population – younger second-generation Muslims – who feel a greater sense of discrimination because of their religion compared to both people from different religions and to their first-generation parents. This makes them a very relevant group to study because of the effects of this discrimination on socioeconomic and educational integration.